The value of biotic pollination and dense forest for fruit set of Arabica coffee: A global assessment - Moreaux, Céline; Meireles, Desirée A.L.; Sonne, Jesper; Badano, Ernesto I.; Classen, Alice; González-Chaves, Adrian; Hipólito, Juliana; Klein, Alexandra-Maria; Maruyama, Pietro K.; Metzger, Jean Paul; Philpott, Stacy M.; Rahbek, Carsten; et al. (Agriculture, Ecosystems & Environment, 2022)
Animal pollinators are globally threatened by anthropogenic land use change and agricultural intensification. The yield of many food crops is therefore negatively impacted because they benefit from biotic pollination. This is especially the case in the tropics. For instance, fruit set of Coffea arabica has been shown to increase by 10–30% in plantations with a high richness of bee species, possibly influenced by the availability of surrounding forest habitat. Here, we performed a global literature review to (1) assess how much animal pollination enhances coffee fruit set, and to (2) examine the importance of the amount of forest cover, distance to nearby forest and forest canopy density for bee species richness and coffee fruit set. Using a systematic literature review, we identified eleven case studies with a total of 182 samples where fruit set of C. arabica was assessed. We subsequently gathered forest data for all study sites from satellite imagery. We modelled the effects of open (all forest with a canopy density of ≥25%), closed (≥50%) and dense (≥75%) forests on pollinator richness and fruit set of coffee. Overall, we found that animal pollination increases coffee fruit set by ~18% on average. In only one of the case studies, regression results indicate a positive effect of dense forest on coffee fruit set, which increased with higher forest cover and shorter distance to the forest. Against expectations, forest cover and distance to open forest were not related to bee species richness and fruit set. In summary, we provide strong empirical support for the notion that animal pollinators increase coffee fruit set. Forest proximity had little overall influence on bee richness and coffee fruit set, except when farms were surrounded by dense tropical forests, potentially because these may provide high-quality habitats for bees pollinating coffee. We, therefore, advocate that more research is done to understand the biodiversity value of dense forest for pollinators, notably assessing the mechanisms underlying the importance of forest for pollinators and their pollination services. •In a meta-study, we gathered 11 case studies that assessed fruit set of C. arabica.•We assessed effects of pollinators and forest on coffee fruit set within each study.•Globally, we found that animal pollination increases coffee fruit set by ~18%.•One study indicates that forest with a dense canopy may benefit coffee pollination.•We suggest more research on the biodiversity value of dense forest for pollinators.